Accurate Delineation of Glioma Infiltration by Advanced PET/MR Neuro-Imaging (FRONTIER Study): A Diagnostic Study Protocol. Issue 4 (October 2016) - Verburg, Niels; Pouwels, Petra J.W.; Boellaard, Ronald; Barkhof, Frederik; Hoekstra, Otto S.; Reijneveld, Jaap C.; Vandertop, W. Peter; Wesseling, Pieter; de Witt Hamer, Philip C.
Abstract : BACKGROUND: Glioma imaging, used for diagnostics, treatment planning, and follow-up, is currently based on standard magnetic resonance imaging (MRI) modalities (T1 contrast-enhancement for gadolinium-enhancing gliomas and T2 fluid-attenuated inversion recovery hyperintensity for nonenhancing gliomas). The diagnostic accuracy of these techniques for the delineation of gliomas is suboptimal. OBJECTIVE: To assess the diagnostic accuracy of advanced neuroimaging compared with standard MRI modalities for the detection of diffuse glioma infiltration within the brain. METHODS: A monocenter, prospective, diagnostic observational study in adult patients with a newly diagnosed, diffuse infiltrative glioma undergoing resective glioma surgery. Forty patients will be recruited in 3 years. Advanced neuroimaging will be added to the standard preoperative MRI. Serial neuronavigated biopsies in and around the glioma boundaries, obtained immediately preceding resective surgery, will provide histopathologic and molecular characteristics of the regions of interest, enabling comparison with quantitative measurements in the imaging modalities at the same biopsy sites. DISCUSSION: In this clinical study, we determine the diagnostic accuracy of advanced imaging in addition to standard MRI to delineate glioma. The results of our study can be valuable for the development of an improved standard imaging protocol for glioma treatment. EXPECTED OUTCOME: We hypothesize that a combination of positron emission tomography, MR spectroscopy, and standard MRI will have a superior accuracy for glioma delineation compared with standard MRI alone. In addition, we anticipate that advanced imaging will correlate with the histopathologic and molecular characteristics of glioma. ABBREVIATIONS: CHO, [11C-]Choline CRF, case report forms FET, [18F-]Fluoroethyl-tyrosine FLAIR, fluid-attenuated inversion recovery METC, Medical Ethical Committee MRS, magnetic resonance spectroscopy PET, positron emission tomography VUmc, VU University Medical Center